Development of a highly effective anti-aging and soothing recombinant Col III - Yuefeng Wang; Jing Zhang; Guoxia Xu; Ruiyan Wang; Wei Zhou (Discover Applied Sciences)
Abstract Collagen provides essential structural support to tissues and the extracellular matrix while participating in various biological processes, making it valuable in biomedicine, tissue engineering, and cosmetics. However, collagen extracted through conventional methods exhibits poor water solubility, potential immunogenicity, and limited production capacity, which restrict its applications and further development. In this study, a novel collagen sequence was designed by enriching active fragments that bind integrins in human type III collagen. The Pichia pastoris (P. pastoris) strain was employed to produce recombinant type III collagen (recombinant Col III), achieving an environmentally friendly collagen production process and further evaluating its safety and efficacy in cosmetic applications. The results demonstrated that recombinant Col III exhibited no cytotoxicity or skin irritancy. It significantly enhanced the migration and adhesion of HaCaT cells while upregulating the expression of claudin-1 (CLDN1), aquaporin 3 (AQP3), filaggrin (FLG), and hyaluronan synthase 2 (HAS2), all of which are intracellular barrier-moisturizing genes, thereby promoting barrier repair and hydration. Additionally, recombinant Col III markedly increased the expression of elastin as well as type I and type III collagen in human dermal fibroblasts, facilitating extracellular matrix regeneration. Furthermore, recombinant Col III significantly reduced the expression of inflammatory cytokines, including prostaglandin E2 (PGE-2), tumor necrosis factor-alpha (TNF-α), and interleukin-1 beta (IL-1β), findings that suggest enhanced anti-inflammatory and soothing effects on damaged skin. In conclusion, recombinant Col III demonstrates significant potential in skin barrier repair, hydration, anti-wrinkling, and anti-inflammatory applications, highlighting its promise as a functional ingredient in cosmetic formulations.